the use and non-use of second language teaching through ‘the first step’ - Rubavathanan, M.; Abeyweera, G.H. (University of Jaffna, 2012)
Certain policies have been adopted by deferent electronic media institution with a view to enhance national integration. One of the policies adopted by the said is the ‘Language Policy’. The national integration is done by various means by media institutions. ‘The First Step’ is one such means where Trilingual policy has been implemented in an advertisement telecast and broadcast in MTV and MBC PLC. Channels before the programme ‘The News First’. This study attempts to provide a detailed syntactic and semantic analysis of the use and non-use of the advertisement ‘The First Step’.
Keywords: Language policy; Trilingual policy